Diglosia dalam Musik Arab Kontemporer: Analisis Bahasa Fusha dan Amiyah dalam Lagu Abeer Nehme - Nailurrahmi, Fitma; Mustafa, Izzuddin; Nandang, Ade (Moderasi : Journal of Islamic Studies, 2025)
This study investigates the interplay between two varieties of Arabic, Modern Standard Arabic (Fusha) and the Lebanese colloquial dialect (Amiyah) in the lyrics of two songs by Lebanese singer Abeer Nehme: “Bi Saraha” and “Bala Ma Nhess”. Using a descriptive qualitative approach grounded in sociolinguistic theory, particularly the framework of diglossia, the research aims to uncover how these language varieties are blended and what sociocultural meanings they carry. Data were collected from official transcriptions of the song lyrics and analyzed linguistically and contextually. The findings reveal a consistent dominance of Amiyah throughout the lyrics, primarily used to express everyday emotions, familiarity, and personal experiences. In contrast, Fusha is inserted selectively to emphasize poetic, spiritual, or symbolic moments within the songs. This selective usage illustrates a deliberate artistic strategy rather than random code-switching, reflecting broader patterns of language use in Arab popular culture. The combination of these two varieties not only enriches the aesthetic quality of the music but also symbolizes the negotiation between personal identity and collective cultural heritage. Furthermore, the analysis suggests that Arabic popular music serves as a powerful medium for expressing linguistic hybridity and for navigating the tension between tradition and modernity. By situating these findings within the larger discourse of Arabic diglossia, the study contributes to a deeper understanding of how music becomes a living space for language practice, identity expression, and cultural reflection in contemporary Arab society.